Contribution of arbuscular mycorrhizal symbiosis to in vitro root metal uptake: from trace to toxic metal conditions - Audet, Patrick; Charest, Christiane (Université d'Ottawa | University of Ottawa, 2009)
This in-vitro study investigated the role of arbuscular mycorrhizal (AM) symbiosis in root metal acquisition and stress tolerance from two experiments using a carrot root-organ culture system, and involving the essential micronutrient zinc as a typical metal contaminant. We demonstrated that the AM symbiosis plays a dual role in root metal acquisition by increasing nutrient uptake via mycorrhizal “enhanced uptake” at low (trace) metal concentrations in the growth medium, but then lessening the uptake through “metal-binding” processes at high (toxic) concentrations. Furthermore, we also observed the relative contribution of hyphal uptake and translocation to roots, which led us to suggest that the enhanced uptake and metal-binding processes likely occur simultaneously and (or) independently. Ultimately, symptoms of metal toxicity toward both the roots and AM fungi at the highest Zn exposure concentrations was observed. From this finding, a critical toxicity burden likely exists arising from conditions ranging from trace to toxic metal extremes.
Keywords: stress avoidance; critical toxicity burden; metal bioavailability; Glomus intraradices; Daucus carota L.